Indeks Kesesuaian Wisata Di Pantai Pemuteran Buleleng, Bali - Maha Putra, I Kadek Aldi Wahyu Andika; Dirgayusa, I Gusti Ngurah Putra; Dharma, I Gusti Bagus Sila (Journal of Marine Research and Technology; Vol 6 No 2 (2023): AGUSTUS 2023, 2023)
Marine ecotourism is one way of developing tourism in coastal areas that pays attention to ecology and maintains environmental stability. This study was conducted to determine the value of the Tourism Suitability Index (IKW) at Pemuteran Beach, Grokgak, Buleleng by considering 10 parameters such as water depth, beach type, beach width, water base material, water current velocity, beach slope, water brightness, coastal land cover, hazardous biota, and freshwater availability. The method of determining the location using the purposive sampling method is by taking an intentional and determined sample so that what you want to study can be represented by the number of stations, as many as 4 station points. The IKW analysis in this study refers to the suitability classification of coastal tourism and the tourism suitability matrix. Based on the results of the IKW analysis at Pemuteran Beach, each station, namely Station I has a value of 77%, station II is 79%, station III is 83%, and Station IV is 82%. It has the type and basic material of the beach with a black sand substrate with a mixture of coral fragments with a depth of 1.55-1.7 m; including shallow waters, the average width of the beach is quite wide, which is 11.5 m. In addition to this, Pemuteran Beach has a coastal slope of less than 10o with an average current speed of 0.27 m/s and has 100% water clarity. Coastal land cover is generally in the form of resident settlements.